An Extremely Pseudo‐Plastic, Organic Crystal‐Based Concentric‐Ring‐Resonator Coupled Optical Waveguide - Avulu Vinod Kumar; Deepak Manoharan; Ankur Khapre; Soumyajit Ghosh; Rajadurai Chandrasekar (Advanced Physics Research)
Abstract The precise shaping of optical waveguides is crucial for advancing photonic circuit technologies. In this study, the first fabrication of a resonator is introduced with coiled circular geometry(CCG) using pseudo‐plastic microcrystals of 6,6′‐((1E,1′E)‐hydrazine‐1,2‐diylidenebis(methaneylylidene))bis(2,4‐dibromophenol), HDBP. The molecular packing supported by type‐II inter‐molecular halogen bonding and hydrogen bonding provides an exceptional strain‐holding capacity for HDBP crystals. This property enables the creation of compact CCGs with three interconnected turns utilizing an atomic force microscopy cantilever tip‐based mechanophotonics technique. This CCG acts as a concentric ring‐resonator (CRR) that splits and routes light in clockwise and anticlockwise directions along circular turns, providing optical interference. Subsequently, an HDBP optical waveguide is integrated with the CRR, resulting in the development of the organic crystal‐based optical filter. The modulation observed in optical modes’ wavelengths and their intensities in the waveguide when coupled with CRR shows optical filter functionality. This fabricated device holds promise for applications in high‐fidelity sensing, precision micro‐measurements, and optical quantum processing technologies, showcasing the potential of organic crystals in advancing photonics.